2021
DOI: 10.3390/medicina57080808
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Patterns in Patients with Neurally Mediated Syncope

Abstract: The baseline electrocardiogram (ECG) is less informative in neurally mediated syncope (NMS) than in arrhythmic syncope. However, some of the ECG patterns present in NMS can have diagnostic and prognostic value in such patients. Electrocardiographic documentation of a syncopal spell and thus identification of the ECG changes can be performed during tilt table test (TTT) or during prolonged ECG monitoring. This work reviews the specific ECG patterns in NMS, which are primarily related to the cardioinhibitory ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In particular, in syncope with delayed VVR, the cardioinhibitory type of VVR [cardioinhibitory response (CI)] seems more serious than the vasodepressor type of VVR [vasodepressor response (VD)], even though previous studies have shown that both types pose a sizable risk of inducing adverse outcomes ( 9 ). However, since CI manifests as cardiac arrest and advanced atrioventicular (AV) node blocks that might lead to sudden cardiac death, CI has been considered more serious than VD ( 9 ). Thus, it has been postulated that the delayed form of VVR syncope may cause CI.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in syncope with delayed VVR, the cardioinhibitory type of VVR [cardioinhibitory response (CI)] seems more serious than the vasodepressor type of VVR [vasodepressor response (VD)], even though previous studies have shown that both types pose a sizable risk of inducing adverse outcomes ( 9 ). However, since CI manifests as cardiac arrest and advanced atrioventicular (AV) node blocks that might lead to sudden cardiac death, CI has been considered more serious than VD ( 9 ). Thus, it has been postulated that the delayed form of VVR syncope may cause CI.…”
Section: Introductionmentioning
confidence: 99%